Blast Cell-surface and Plasma Soluble Urokinase Receptor in Acute Leukemia Patients: Relationship to Classification and Response to Therapy - Mustjoki, Satu; Alitalo, Riitta; Stephens, Ross W.; Vaheri, Antti (Thrombosis and Haemostasis, 1999)
Plasminogen activation in leukemia has been less well characterized than in other malignancies. However, the increased tendency to bleeding and tissue infiltration by leukemic cells are processes in which plasminogen activation may be involved. We have examined plasma and the peripheral blood mononuclear cell fraction from 80 patients including 53 patients with newly diagnosed acute leukemia and 27 patients with other hematological disorders as well as 21 healthy controls. In 28 of 29 examined patients with acute myeloid leukemia (AML) and in two of three patients with hybrid leukemia we found urokinase receptor (uPAR) on the cell surface, while most (7/9) samples from patients with acute lymphoblastic leukemia (ALL) were negative for uPAR. The plasma mean value for soluble uPAR (suPAR) was significantly elevated in patients with AML and ALL. In AML the highest values were found in patients who had residual disease after several cycles of chemotherapy. Compared to controls the uPA antigen levels in patient plasmas were elevated and decreased along with uPAR during treatment. Our results suggest that cell surface uPAR may be a useful marker for leukemia classification and in our material a high level of plasma suPAR correlated with resistance to chemotherapy in AML.